Health Literacy among Diabetic Patients at the Family Practice Center of Phra Nakhon Si Ayutthaya Hospital - วงศ์นิศานาถกุล, กิตติพศ (Journal of Preventive Medicine Association of Thailand, 2018)
Diabetes mellitus is one of the important noncommunicable diseases (NCDs) that requires good control of diabetes to prevent complications that affect not only quality of life of diabetic patients but also the national economy. Patients with good health literacy tend to have better communication with physicians and be able to modify their behavior to achieve diabetes treatment goals. The aim of this study was to find out the health literacy level and factors associated with health literacy among diabetic patients at the family practice center, a primary care unit of Phra Nakhon Si Ayutthaya Hospital, in Phra Nakhon Si Ayutthaya Province. This study design was a cross-sectional study. The data collection was performed in 133 patients with type 2 diabetes mellitus at the family practice center during November December 2017. The randomization was done by selecting only patients with even number queue cards. The research tool was derived from the health literacy questionnaire for patients with diabetes and hypertension, developed by the Health Service Support Department, Ministry of Public Health and Mahidol University. The data were analyzed by using descriptive statistics and inferential statistics (Chi-square test or Fisher’s exact test). The study result showed that 19.5 percent of diabetic patients at the family practice center had high health literacy level, while 80.5 percent had low health literacy level. The statistically significant factors related to health literacy level in diabetic patients were age, gender, education level, occupation, monthly income, smoking habits, and hypertension (p-value<0.05). Only 21.1 percent of diabetic patients had good health behavior and there was a statistical relationship between health literacy level and health behavior (p-value<0.001). It is necessary to promote health literacy programs for diabetic patients in NCDs services in the future.